How Filipino adolescents communicate with their parents, and vice-versa, topics about sexual behavior and reproductive health - Arguilla, Sergio Manuel Q. 1993-; Habitan, Jake Zakk M. (2014)
"This study examines how 15-19 year old Filipino adolescents belonging to socio-economic class D communicate with their parents, and vice-versa, regarding topics about sexual behaviour and reproductive health. The study describes the role of parents, adolescents, and other people involved and looked into the topics of the parent-adolescent communication. The study also explored the factors that contribute to the difficulties parents and adolescents experience when dealing with the abovementioned topics, and how they resolve them. The study employed two theories: Riley and Riley's Model of Communication and Baxter and Montgomery's Relational Dialectics. The theories provided the premise for the communication between parents and adolescents, including other relatives, peers, and other people as the social context of the communication and the premise for the difficulties parents and adolescents encounter in the communication. Purposeful sampling was used to determine the informants of the study, which include Filipino adolescents (15-19 years old) and Filipino parents with adolescent offspring. Semi-structured in-depth interviews were employed by the study. The study found that both parents and adolescents can initiate the communication, and the topics they discuss range from biological, to relational and family, to preventive and risk, to sexuality, and up to the societal aspect. It was also found that parents and adolescents encounter difficulties in communicating ranging from lack of knowledge to discomfort, which they resolve by spending more timwe with each other, and using humor in conversations."